Sobre sexo, cachorros, estômago e amores: o amarelo bruto da cidade contemporânea: uma leitura da marginalidade nos filmes Amarelo Manga e Amores Perros (Amores Brutos) - Pinto, Pedro Henrique Pinheiro Xavier (2011)
This paper aims to discuss the urban marginality in Latin America, representatives from the cinema of marginality and its aesthetic of dirty realism. The films chosen for the analysis are: Amarelo Manga (2002) and Amores Perros (2000). To this end, there will be a reading of modernity, cinema and cities, as well as the very aesthetic of dirty realism and film of marginality. At another point, we discuss issues related to urban studies in, theories of marginality, configuration establisehd/outsiders, and feelings of insecurity, risk and fear, from sociological references. Finally, the analysis will be made of the films, within the guidelines of the methodology of film analysis.